Effects of dissolved mercury on embryogenesis, survival, growth of Mytilus galloprovincialis mussel larvae - Beiras, Ricardo; His, Edouard (Inter-Research, 1995)
The effects of Hg concentrations ranging from 0 (control) to 1024 µg 1-1 upon embryogenesis, survival and growth of Mytilus galloprovincialis mussel larvae were investigated . Embryogenesis was abnormal in 50 % of the individuals at 10µg 1-1. The 48 h LC50 for D-shaped, early umbonate, late umbonate and eyed larvae were 51, 164, 322 and 383 µg 1- 1 respectively. The LC50 was an allometric function of ash-free dry weight with exponent b = 0.60. Larval growth was significantly reduced alter 6 d exposure to 4 µg Hg 1-1 and alter 10 d exposure to 2 µg 1-1. No significant differences in lethal or sublethal sensitivity to Hg were found between M. galloprovincialis and previously studied Crassostrea gigas embryos and larvae. The implications of these findings for monitoring pollution by utilising different bivalve species are discussed.